Pullulan as a stabilizer agent of polymeric nanocapsules for drug delivery (Brazilian Journal of Pharmaceutical Sciences, 2016)
Polymeric stabilizers have received attention in the preparation of nanostructured systems due to their ability to enhance formulation stability. Considering this, the objective of this work was to prepare poly(ε-caprolactone) nanocapsules using the pullulan as a polymeric stabilizer. The nanocapsules were prepared using the interfacial deposition method of preformed polymers and they were characterized in terms of pH, average diameter, polydispersity index, zeta potential, beclomethasone dipropionate content, encapsulation efficiency, photostability and drug release profiles. The formulations showed physicochemical characteristics consistent with nanocarriers for drug delivery such as: average diameter lower than 270 nm, polydispersity indexes lower than 0.2, negative zeta potential (-22.7 to -26.3 mV) and encapsulation efficiencies close to 100%. In addition, the nanocapsules were able to delay the beclomethasone dipropionate photodegradation under UVC radiation and by the dialysis bag diffusion technique, the nanocapsules were able to prolong the drug release. Thus, pullulan could be considered an interesting excipient to formulate polymeric nanocapsules.